Służba cywilna w Polsce. Kierunki zmian - Jurga-Wosik, Ewa (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The civil service in Poland lacks legal and institutional continuity. Four laws regarding the civil service have been enacted over the past twelve years which have made different provisions concerning, for example, the body in charge of the civil service (The Civil Service Supervisor or the Head of the Chancellery of the Prime Minister) and handling its matters (The Civil Service Office of the Chancellery of the Prime Minister), the status of higher posts (in the civil service and outside of it) and the manner of manning such posts (contests, appointments, enrollment). The act on the civil service of 2008 introduced a range of instruments to provide for consistent operations and, consequently, stability of human resource management. It should be emphasized that at present the challenge concerning the civil service is to prepare it for the tasks to be fulfilled while Poland holds the presidency of the Council of the European Union. Providing training and applying various methods to develop civil servants’ competence as well as adopting European models are a chance to increase the quality of civil service operations.